The Sundanese weekly magazine "Manglé"; Fostering the growth of Sundanese literature as part of Indonesian cultural history - Rahayu, Taufik (Wacana, Journal of the Humanities of Indonesia, 2025)
Reflecting on the evolution of the weekly Sundanese magazine, Manglé, since its establishment in 1957, this article traces the magazine’s vital role in fostering the growth of modern Sundanese writing. For the past 66 years, it has provided a platform for Sundanese writers to showcase their works, with numerous prominent authors gracing its pages. At the peak of its success in 1964, Manglé had a circulation of 70,000 copies, but its circulation has dwindled over time. The advent of the internet and social media has presented new challenges, compelling Manglé to struggle to recapture its former glory. However, the magazine remains an irreplaceable guardian of Sundanese literature and culture and fulfills a role that national media outlets cannot play. Sundanese writers choose Manglé to publish their Sundanese pieces, in preference to writing in Indonesian for broader circulation. This promotion of Sundanese writing can be traced chronologically through the influence and views of the editors-in-chief. Manglé’s unwavering championing of Sundanese language and literature is exemplary, and its continuing commitment to sustaining and supporting Sundanese socio-cultural events deserves proper recognition.